2012
DOI: 10.1111/j.1540-8175.2012.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy as Rescue Therapy in End‐Stage Heart Failure: Illustration by Three‐Dimensional Speckle Tracking Strain Echocardiography

Abstract: We report the case of a 73-year-old man admitted for refractory heart failure following implantation of a dual-chamber pacemaker. Three-dimensional (3D) echocardiography with speckle tracking area strain identified severe left ventricular (LV) dysfunction and LV dyssynchrony following right ventricular pacing. As the patient's clinical condition rapidly worsened despite optimal medical treatment, a cardiac resynchronization therapy (CRT) pacemaker was successfully implanted as rescue therapy. Symptoms rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…No trials have reported on the usefulness of LV dyssynchrony prior to CRT implantation in patients with NAHF. One case report described a 73‐year‐old man with a pacemaker who was admitted for refractory heart failure [16]. A speckle tracking strain identified severe LV dysfunction and LV dyssynchrony following RV pacing.…”
Section: Discussionmentioning
confidence: 99%
“…No trials have reported on the usefulness of LV dyssynchrony prior to CRT implantation in patients with NAHF. One case report described a 73‐year‐old man with a pacemaker who was admitted for refractory heart failure [16]. A speckle tracking strain identified severe LV dysfunction and LV dyssynchrony following RV pacing.…”
Section: Discussionmentioning
confidence: 99%
“…There have now been multiple cases showing that this hemodynamic benefit can be significant enough to liberate patients tethered to vasopressors, inotropes, or even ECMO and achieve stability enough to leave the intensive care unit (Table 5). [69][70][71][72][73][74][75][76] We describe the case of a patient in our ICU on multiple vasopressors, inotrope, and IABP with wide paced morphology who could not be weaned until BiV upgrade (Figure 2). Another retrospective study from Japan, examined 50 patients that were all ICU level patients with wide QRS who were unable to be discharged from intensive care (due to requiring IABP or inotropes).…”
Section: Biventricular Pacingmentioning
confidence: 99%
“…The suitability of echocardiographic parameters to improve the response rate to CRT has been controversial. Speckle tracking echocardiography (STE) has been reported as a useful imaging method to detect CRT responders [ 3 , 4 ]. Atrioventricular (AV) and interventricular (VV) delay optimization can augment ventricular function in CRT and is usually performed utilizing echocardiography [ 5 ].…”
Section: Introductionmentioning
confidence: 99%